PECULIARITIES OF THE DEVELOPMENT OF GASTRONOMIC TOURISM IN GEORGIA - Boyko, Z. V.; Horozhankina, N. A.; Korneyev, M. V.; Shcholokova, H. V.; Umanska, S. O. (Systems and Technologies, 2024)
The article examines the essence of gastronomic tourism and its structure, considers its various definitions developed by foreign and domestic scholars. Gastronomic tourism is one of the types of excursion and educational tourism that was formed at the end of the 20th century. This is a relatively new but extremely interesting direction of the tourism business, which is actively developing, allowing travellers to learn about the cuisine of different countries and ethnic groups. The research uses the methods of structural-logical and semantic analysis (to clarify the terminology and conceptual apparatus of gastronomic tourism); system analysis (to assess the current state and prerequisites for the development of GT in Georgia), statistical method (to assess the place of GT in the tourist industry of Georgia), graphic method (for visual presentation of statistical data). The formation and development of gastronomic tourism in the world, its importance for the formation of the image of the territory are analysed. It is determined that gastronomic tourism is an integral part of all tours, and gastronomy has the potential to increase the attractiveness of the tourist product and tourist destination in general. It is proved that creating a favourable image of a country through the prism of national cuisine is a successful marketing ploy that helps attract tourists. It is intended, on the one hand, for tourists seeking knowledge and experience of new cultures, and, on the other hand, it provides additional value to the brands of tourist destinations. The influence of international (the World Food Travel Association and others) and national gastronomic tourism organisations on its development is characterised. The place of gastronomic tourism in the tourism industry of Georgia and the prospects for its development are analysed. It is proved that the culinary and wine sectors of Georgia play an important role. Thus, the contribution of the "Food and beverage service activities" sector in recent years has been approximately 20% in the GDP structure of the tourism industry. The analysis of the Georgian tourism sector has shown that gastronomic tourism in Georgia has significant potential to contribute to the development of new quality tourism products and experience. For its part, the National Tourism Administration of Georgia is doing its utmost to promote gastronomic tourism both nationally and internationally.